Risk Committee and Risk Disclosure Quality: Evidence from Listed Insurance Firms in Nigeria - Wada, Najib Abbas; Rabiu, Naja'atu Bala; Dandago, Kabiru Isa (Universitas Syiah Kuala, 2023)
Objective This study investigated the impact of risk committee characteristics on the risk disclosure quality (RDQ) of listed insurance firms in Nigeria from 2011-2021.Design/Methodology Data for the research was generated from the annual reports and financial statements of seventeen listed insurance firms sampled out of a population of twenty-one. The study employed descriptive summary statistics, correlation analysis, regression analysis and factor analysis to analyze the data gathered.Results Using factor analysis, it was found that Risk Disclosure Quantity (RDQUANT) has the highest eigenvalue, making it the composite quality of the risk disclosure of listed insurance firms and denoting that the RDQ of insurance firms is best measured by the RDQUANT. Using GLS regression, it was found that Risk Committee Size (RCS) and Risk Committee Meeting (RCM) have a significant positive impact on the RDQ of Listed Insurance firms in Nigeria. Contrary, Risk Committee Executive Presence (RCEXP) has an insignificant negative impact on the RDQ of the listed insurance firms.Research limitations/implications This result influences the efforts of regulatory authorities in their attempt to develop resilient corporate governance codes that guarantee qualitative risk disclosures. The study recommends that regulatory authorities in the Nigerian insurance industry should mandate the establishment of large risk committees and set higher thresholds for committee meetings over and above the traditional quarterly meeting. The risk committee should be composed of a lower number of executive directors.Novelty/Originality The originality of this study lies in the usage of factor analysis to determine the best measure of risk disclosure quality in Nigeria. In addition, this is the first study of its kind to determine the impact of risk committee attributes on risk disclosure quality in the Nigerian Insurance industry.